2018
DOI: 10.3329/jbau.v16i1.36479
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of genetic variability, correlation and path coefficient analysis in local landraces of rice (Oryza sativa L.) for the improvement of salinity tolerance

Abstract: Twenty eight local rice landraces were assessed for eleven morphological traits for the improvement of salt tolerance ability of rice genotypes. Genotypic variance (σ 2 g), phenotypic variance (σ 2 p), phenotypic co-variance (PCV), genotypic co-variance (GCV), heritability, genetic advance, genetic advance as a percentage of mean, correlation coefficient and path coefficient were estimated. For all the traits, PCV was higher than the GCV indicating that they were controlled by non-additive gene action and sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 7 publications
3
8
0
Order By: Relevance
“…Different independent traits, such as survival, shoot length, shoot dry weight, root length, SPAD value, Na + concentration, K + concentration, and Na + /K + ratio, directly and indirectly contributed to the salt tolerance (dependent trait). Thus, the total salt tolerance is the sum of these eight characteristics and includes a residual effect (R), which is consistent with earlier research [ 55 , 56 , 57 , 58 , 59 ]. A path coefficient analysis revealed that survival, Na + concentration, K + concentration, and Na + /K + ratio are the most crucial features for estimating the degree of salt tolerance, as these variables collectively account for the majority of phenotypic variance.…”
Section: Discussionsupporting
confidence: 90%
“…Different independent traits, such as survival, shoot length, shoot dry weight, root length, SPAD value, Na + concentration, K + concentration, and Na + /K + ratio, directly and indirectly contributed to the salt tolerance (dependent trait). Thus, the total salt tolerance is the sum of these eight characteristics and includes a residual effect (R), which is consistent with earlier research [ 55 , 56 , 57 , 58 , 59 ]. A path coefficient analysis revealed that survival, Na + concentration, K + concentration, and Na + /K + ratio are the most crucial features for estimating the degree of salt tolerance, as these variables collectively account for the majority of phenotypic variance.…”
Section: Discussionsupporting
confidence: 90%
“…In contrast, the research we have conducted does not support the idea by Augustina et al (2013) that panicle length and grain yield are negatively correlated. Additionally, the scientist discovered a weak and positive correlation between plant height and grain yield as well as a weakly significant correlation between days to 50% heading and grain yield, all of which are similar to our findings (Rasel et al, 2018). However, there was a slight and substantial negative significant correlation between panicle weight (r=-0.096) and thousand-grain weight (r=-0.192) with grain yield.…”
Section: Correlation Between Grain Yield and Other Traitssupporting
confidence: 89%
“…This finding is consistent with previous reports on rice [ 39 ]. According to [ 40 ], the coefficients of phenotypic variation are low below 11%, moderate between 11 and 20%, and high above 20%. The coefficient of phenotypic variation was higher than the coefficient of genotypic variation for all traits.…”
Section: Discussionmentioning
confidence: 99%